FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MELAKUKAN WHISTLEBLOWING - Ridha Aurila; Devi Narulitasari (AKUNTABILITAS, 2022)
This study aims to determine the factors that influence students' intention to do whistleblowing. The population in this study were all accounting students from several Colleges of Economics (STIE) in Surakarta who had participated in auditing 1 and auditing 2. The sampling technique used was purposive sampling and a sample of 84 respondents was obtained. This study uses a questionnaire as data collection material. The results showed that attitudes toward behavior and subjective norms had a positive and significant effect on whistleblowing intentions. While the perception behavioral control has not effect on the intention to do whistleblowing. The results also showed that the perception of organizational support and machiavellianism negatively affected whistleblowing intentions. This research is expected to add insight and knowledge in the field of accounting, especially in auditing and behavioral accounting about the factors that influence the intention to do whistleblowing. Otherwise, it can be taken into consideration in conducting whistleblowing